Resting energy expenditure in subjects with fibro‐calculous pancreatic diabetes (胰腺纤维钙化性糖尿病患者的静息时能量消耗). (30th July 2013) - Behera, Kishore Kumar; Joseph, Mini; Shetty, Sudeep Krishna; Chacko, Ashok; Sahoo, Manoj Kumar; Mahendri, Narayani V; Nair, Veena; Nadig, Shweta; Thomas, Nihal
Abstract Background Fibro‐calculous pancreatic diabetes is an indigenous disorder present in populations largely in tropical regions. Energy expenditure through indirect calorimetry has not been studied in this disorder and may provide important clues as to the pathogenesis of diabetes in these patients. Methods A total of 51 males in three groups comprising fibrocalculous pancreatic diabetes (FCPD) (group 1; n = 24), type 2 diabetes (group 2; n = 15) and healthy controls (group 3; n = 12) were studied. The body composition was measured using Dual Energy X‐ray Absorptiometry (DEXA) and the REE was estimated using indirect calorimetry. The predicted energy expenditure (PEE) was calculated using three different equations. Results Patients in both groups with diabetes had a higher mean waist‐hip ratio than the controls (P = 0.002). However patients with type 2 diabetes alone had a significantly higher mean body mass index (P = 0.012), percentage of fat (P = 0.016) and total fat content (P = 0.031). There was no significant difference in REE among the three groups. After adjustment of body mass index (BMI), the REE was significantly higher in patients with FCPD than in those patients with Type 2 diabetes. PEE correlated poorly with indirect calorimetry. Conclusions Energy expenditure in patients with diabetes varies according to the composition and distribution of body fat and is lower in patients with FCPD. Standard predictive equations were not accurate for the assessment of energy expenditure in patients with FCPD. Further research is required to recommend specific nutritional therapy for this group of patients.